Pengembangan Sistem Informasi Penjualan Online Untuk Produk Lokal Papua: Pendekatan Waterfall - Petrus, Risma; Mardewi; Marhaba, Melvi (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Micro, small and medium enterprises are part of the business that has an important role in the national economy. Currently, MSMEs through government programs continue to be attempted to be run in all regions in Indonesia. One of the regions that is involved in running the MSME program is the Papua region. The purpose of the research conducted is to design a sales system for local Papuan products that can improve the economy in the Papua region from the crafts of the people in the Papua region using an online-based sales concept. The system development method used is the waterfall method which begins with the stages of needs analysis, system design, implementation, testing and maintenance. The results of the research obtained from this study are to promote local Papuan-style products from the eastern region using a website so that they can be reached by all groups. Through this research, it is obtained that by using a seller system, it makes it easier for business actors in the Papua region to market their products and through this system, they can introduce local Papuan products to a wider market, increase competitiveness and ultimately encourage the local economy, and be useful for research in the field of information technology which can then carry the diversity of local wisdom products.